Safety assessment of buried gas pipeline subject to surface explosion: A case study in Wuhan, China. (February 2021) - Tang, Qichen; Jiang, Nan; Yao, Yingkang; Zhou, Chuanbo; Luo, Xuedong; Wu, Tingyao
Highlights: Full scale field surface explosion experiment is conducted. The reliability of the numerical model and parameters are proved by field tests. The controlled explosive charge on the surface above the pipeline is obtained. Abstract: To ensure the safety of the underground gas pipeline in urban ground explosion construction and terrorist attack, a study of the safety of buried gas pipelines under surface explosions is inevitable. In this paper, an operating gas pipeline in Wuhan Economic Development Zone is taken as an example, and the surface explosion full-scale experiment is carried out in the open site. In the field experiment, small charge of No. 2 rock emulsion explosives were used to simulate ground construction blasting, the blasting vibration velocity tester (TC-4850) and dynamic strain measurement system (DH5956) are used to monitor data, the analysis of field data shows that the experimental data meet the general rules, which proves the reliability of the field experiment. Secondly, the numerical model of pipeline response characteristics under surface explosion is established, and the reliability of the model is verified by field monitoring data. In the numerical analysis, the operating pressure of 0.2 MPa is given to the pipeline following the actual working condition, and the response characteristics of the pipeline under the condition of large explosive charge blasting on the surface are discussed. Based on the simulation results, the dangerous section and dangerous point of the pipeline under the action of ground explosion are analyzed, and the functional relationship between the peak effective stress (PES) of pipeline dangerous point and the explosive charge on the surface is deduced. Finally, according to the pipeline control value of PES determined in relevant specifications, the controlled explosive charge of surface construction blasting is obtained. Further, the equivalent conversion analysis of No. 2 rock emulsion explosive and TNT explosive is carried out, and the TNT controlled explosive charge of ground terrorist attack is obtained.